Studi Deskriptif Kuantitatif Mengenai Body Dissatisfaction pada Individu dengan Kecenderungan Food Addiction di Indonesia - Alfiah Rahmi Putri; Rida Yanna Primanita (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to determine the level of body dissatisfaction among individuals experiencing food addiction. Food addiction is characterized by impulsive and uncontrolled eating behavior, particularly toward high-fat and high-sugar foods, accompanied by physical and psychological dependence. This condition increases the risk of weight gain and negatively impacts body image, especially among female college students who are vulnerable to social pressure and ideal beauty standards. The research employed a descriptive quantitative approach with incidental sampling techniques. Participants consisted of six female students from the Psychology and Primary School Teacher Education (PGSD) programs at Universitas Negeri Padang, selected based on the food addiction criteria outlined in the DSM-5. The Body Shape Questionnaire (BSQ-16A) was used to measure body dissatisfaction levels. Data were analyzed using percentage distribution to provide a general overview of body dissatisfaction among the research subjects. The results showed that 66.66% of participants experienced high to very high levels of body dissatisfaction. This indicates a positive relationship between food addiction and body dissatisfaction. Students with food addiction tend to have negative perceptions of their body shape, influenced by social pressures, media exposure, and prevailing beauty ideals in society. These findings highlight the need for appropriate psychological interventions and education about healthy eating habits and self-acceptance in university environments. Through a comprehensive approach, it is hoped that students can develop a more positive body image and avoid eating disorders that may harm their physical and mental health. Additionally, this study can serve as a basis for developing mental health promotion programs and eating disorder prevention efforts among university students.